Hospitality and Islam welcoming in God's name - Siddiqui, Mona (Yale University Press, 2015)
"Considering its prominent role in many faith traditions, surprisingly little has been written about hospitality within the context of religion, particularly Islam. In her new book, Mona Siddiqui, a well-known media commentator, makes the first major contribution to the understanding of hospitality both within Islam and beyond. She explores and compares teachings within the various Muslim traditions over the centuries, while also drawing on materials as diverse as Islamic belles lettres, Christian reflections on almsgiving and charity, and Islamic and Western feminist writings on gender issues. Applying a more theological approach to the idea of mercy as a fundamental basis for human relationships, this book will appeal to a wide audience, particularly readers interested in Islam, ethics, and religious studies."--Publisher's Web site